Effect of carbonaceous fillers on adsorption behavior of multifunctional diatomite-based foams for wastewater treatment. (October 2021) - Galzerano, B.; Aprea, P.; Verdolotti, L.; Salzano de Luna, M.; Ascione, C.; Caputo, D.; Lavorgna, M.; Migliore, E.; Liguori, B.
Abstract: Nowadays the study of the potential applications of multifunctional materials for environmental remediation is one of the main goals of the materials engineering. Multifunctional porous materials, MPMs, incorporate, all in once, different and multiple functionalities that make them suitable for several uses and can satisfy many purposes at the same time. Multifunctional diatomite-based foams with a hierarchical porosity, already produced and characterized to be applied in building as well as aerospace sectors, are proposed as adsorbents for inorganic and organic pollutants removal from wastewaters. Then, the effect of the addition of different carbonaceous nanofillers (graphite, graphene and graphene oxide) on the water purification efficiency of the adsorbent was evaluated. Firstly, pristine MPM showed the best performance in adsorbing Indigo Carmine due to its intrinsic chemism and hierarchical porosity (at macro-, micro- and nano-level), but it is not the best with respect to the Cd 2+ adsorption, if compared with the nanocomposites. Among the nanocomposite products, both graphene- and graphene oxide-MPM samples showed a significantly improved adsorption capacity towards Cd 2+ . This behavior is due to the synergistic effect of the finer morphology, higher available foam surface, and the highly exfoliated fillers, graphene and graphene oxide, which permit a better dispersion into the matrix. Graphical abstract: Image 1 Highlights: Novel sustainable absorber multifunctional porous materials-MPMs with a hierarchical porosity. Nanocomposite MPM-absorbers with Graphite, Graphene and Graphene Oxide were obtained. Heavy metal, Cd 2+ and anionic dyes absorption ability of MPM nanocomposite was studied.